Pengaruh Gaya Belajar Anak terhadap Hasil Belajar Tematik Siswa - Moh Junaidi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2018)
Children's learning styles differ from one to another, some have good learning style and some are bad that it may have an influence on student learning outcomes. This research uses a case study and quantitative method. Data collection techniques using observation, interviews, questionnaires, tests etc. which were analyzed descriptively and tested by using the Manova and ANOVA tests using Windows SPSS 16.0. The results of this study indicate that there is an effect of learning styles on student learning outcomes. The value obtained by researchers on the relationship between learning styles and student learning outcomes is 0.173 ≥ 0.05. This value can be interpreted that between learning styles and learning outcomes have high results. It means, learning styles have a significant influence on student learning outcomes. Thus the hypothesis proposed is accepted, namely there is an influence between learning styles on learning outcomes of class IVA and IVB MI NU Habibul Abrori Suko Jogoyudan Lumajang.